A narrative review of anti-obesity medications for obese patients with osteoarthritis. (13th August 2022) - Oo, Win Min; Mobasheri, Ali; Hunter, David J
ABSTRACT: Introduction: The prevalence of both obesity and osteoarthritis (OA) is increasing worldwide (twindemic), and the association between the two chronic diseases is also well established. Areas covered: In this narrative review, we will briefly describe the double burdens of both diseases, the impact of weight loss or gain on OA incidence and structural progression and discuss the biomechanical and anti-inflammatory mechanisms mediating these effects. FDA-approved anti-obesity drugs are summarized in terms of their clinical efficacy and safety profile, and the completed or ongoing phase 2/3 clinical trials of such drugs in OA patients with obesity are examined. Expert opinion: We will discuss the perspectives related to principles of prescription of anti-obesity drugs, the potential role of phenotype-guided approach, time to drug effects in clinical trials, sustainability of weight loss based on the real-world studies, the importance of concomitant therapies, such as dieting and exercises, and the role of weight loss on non-weight bearing OA joints. Although obesity is the major risk factor for OA pathogenesis and progression, and there are a variety of anti-obesity medications on the market, research on the use of these disease-modifying drugs in OA (DMOAD) is still sparse.